2005
DOI: 10.1074/jbc.m505531200
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic Acid Inhibits the Insulin Induction of Glucose-6-phosphate Dehydrogenase via p38 MAP Kinase

Abstract: Insulin is the central hormone required for the activation of lipogenic genes in the liver. Feeding animals a high carbohydrate diet enhances the expression of the lipogenic genes. This effect involves the stimulatory actions of both dietary glucose and insulin (1, 2). In contrast, dietary polyunsaturated fats attenuate the stimulatory effect of feeding a high carbohydrate diet (3, 4). We have used glucose-6-phosphate dehydrogenase (G6PD), 2 a member of the lipogenic gene family, as a model system for studying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 54 publications
(62 reference statements)
4
42
2
Order By: Relevance
“…Previous evidence from our lab demonstrates that the increase in splicing of G6PD that we observe with insulin treatment is due to an increase in its signaling through the PI3K pathway, whereas arachidonic acid treatment attenuates insulin signaling by inhibiting PI3K activity (47). Arachidonic acid decreases the amount of phosphorylated SR proteins and causes a coincident decrease in the accumulation of G6PD mRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…Previous evidence from our lab demonstrates that the increase in splicing of G6PD that we observe with insulin treatment is due to an increase in its signaling through the PI3K pathway, whereas arachidonic acid treatment attenuates insulin signaling by inhibiting PI3K activity (47). Arachidonic acid decreases the amount of phosphorylated SR proteins and causes a coincident decrease in the accumulation of G6PD mRNA (Fig.…”
Section: Discussionmentioning
confidence: 89%
“…In support of a role of p38 MAPK in mediating the effect of CDCA on hepatic lipogenic gene expression, Xiong et al (67) recently showed that activation of p38 MAPK with a constitutively active form of MKK6 inhibits the expression of FAS and SREBP-1c in rat hepatocytes. Interestingly, glucagon and polyunsaturated fatty acids also inhibit the hepatic expression of glucose-6-phosphate dehydrogenase, FAS, and SREBP-1c via a mechanism that is dependent on the presence of p38 MAPK and/or ERK (67)(68)(69). Thus, p38 MAPK and ERK appear to have a general role in inhibitory pathways controlling lipogenic gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…Peptides were accepted if they had a cross-correlation (X corr ) score of at least 1.9, 2.2, or 3.7 for the ϩ1, ϩ2, or ϩ3 charge states, respectively. Western analysis was as previously described (40). The hnRNP antibodies (Immuquest) and SR antibodies (Zymed Laboratories Inc.) were purchased from the indicated sources.…”
Section: Lc-ms/ms and Westernmentioning
confidence: 99%